PERCEIVED THREAT OF COVID-19 AND ITS IMPACT ON EXPEDITION SERVICE COMPANY EMPLOYEES IN JAKARTA - Gatri Lunarindiah; Netania Emilisa; Reniati Karnasi; Karina Ganadi; Dietce Apriani (SEAN Institute, 2023)
This research aims to analyze the impact of the perceived threat of Covid-19 directly or indirectly on workload, job stress, and job satisfaction. The sample in this study was 190 employees who worked at expedition service company employees in Jakarta and were taken using a purposive sampling method. The instrument test used is the validity and reliability test, which uses the PLS-SEM method for testing the hypothesis. The results obtained were that there was no positive effect between the perceived threat of Covid-19 on workload, there was no adverse effect between the perceived threat of Covid-19 on job satisfaction, there was a positive effect from the perceived threat of Covid-19 on job stress, there was no effect negative between workload and job satisfaction, there is no adverse effect between job stress and job satisfaction, workload mediates the effect between perceived threat of Covid-19 on job satisfaction and Job stress does not mediate the effect between perceived threat of Covid-19 on job satisfaction.